2016
DOI: 10.1038/nature19795
|View full text |Cite
|
Sign up to set email alerts
|

On-target efficacy of a HIF-2α antagonist in preclinical kidney cancer models

Abstract: Clear cell renal cell carcinoma (ccRCC), the most common form of kidney cancer, is usually linked to inactivation of the pVHL tumor suppressor protein and consequent accumulation of the HIF2α transcription factor 1. Here we show that a small molecule (PT2399) that directly inhibits HIF2α causes tumor regression in preclinical models of primary and metastatic pVHL-defective ccRCC in an on-target fashion. pVHL-defective ccRCC cell lines display unexpectedly variable sensitivity to PT2399, however, suggesting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
372
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(398 citation statements)
references
References 15 publications
19
372
1
6
Order By: Relevance
“…In general, transcription factors such as HIF2a have generally been considered undruggable therapeutic targets (47). Recently, several reports described the antitumor effects of a small-molecule HIF2a antagonist that binds to a hydrophobic binding pocket discovered in HIF2a PAS-B domain (16,(20)(21)(22). Although these studies showed encouraging results that validated HIF2a as a therapeutic target, certain limitations are apparent.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In general, transcription factors such as HIF2a have generally been considered undruggable therapeutic targets (47). Recently, several reports described the antitumor effects of a small-molecule HIF2a antagonist that binds to a hydrophobic binding pocket discovered in HIF2a PAS-B domain (16,(20)(21)(22). Although these studies showed encouraging results that validated HIF2a as a therapeutic target, certain limitations are apparent.…”
Section: Discussionmentioning
confidence: 96%
“…Although these studies showed encouraging results that validated HIF2a as a therapeutic target, certain limitations are apparent. These included preexisting drug-resistant mutations, posttreatment mutations discovered surrounding the binding pocket of this small molecule, and the dependence of some tumors on cellular pathways other than VHL-HIF (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This inhibitor can suppress the tumor progression in the preclinical models of VHL-inactive ccRCC, and demonstrate much better activity than sunitinib, the first line agent for the ccRCC treatment in clinic. Besides, PT2385, an analogue of PT2399, has already been on-going in the Phase I clinical research by Peloton Therapeutics Cho et al, 2016).…”
mentioning
confidence: 99%